Food labelling complete texts (Food and Agriculture Organization of the United Nations, 2005)
Contains a collection of the standards and guidelines on food labelling to allow their use and understanding by governments, regulatory authorities, food industries, retailers, and consumers. This work covers topics such as labelling of food additives, claims for special dietary uses, nutrition labelling, and the use of the term 'Halal'.